The Historical Basis of the Pre-school Education Development in Kyiv and Kyiv Region in the second half of the 20th and beginning of the 21st century - Venglovs’ka, Olena (Pedagogical Discourse, 2013)
The paper presents the results of a study on the problem of the sources of pre-school education in Kiev and Kiev region in the second half of 20th – beginning of 21st century. Characteristics of different sources are made ​​with current methodological approaches to their classification. In the research the analytical review of published and unpublished documents, which include statistical collections, materials of scientific conferences, workshops on early childhood education, decisions of the Executive Committees of the Kyiv city, regional, district and village Council of People’ Deputies, materials and information on the audit work of kindergartens in Kiev and Kiev region is given. A separate group of the source base are laws and regulations of the Ukrainian SSR and the Ukrainian independence period.